Cell lineage-specific genome-wide DNA methylation analysis of patients with paediatric-onset systemic lupus erythematosus. Issue 4 (3rd April 2019) - Yeung, Kit San; Lee, Tsz Leung; Mok, Mo Yin; Mak, Christopher Chun Yu; Yang, Wanling; Chong, Patrick Chun Yin; Lee, Pamela Pui Wah; Ho, Marco Hok Kung; Choufani, Sanaa; Lau, Chak Sing; Lau, Yu Lung; Weksberg, Rosanna; et al.
ABSTRACT: Patients with paediatric-onset systemic lupus erythematosus (SLE) often present with more severe clinical courses than adult-onset patients. Although genome-wide DNA methylation (DNAm) profiling has been performed in adult-onset SLE patients, parallel data on paediatric-onset SLE are not available. Therefore, we undertook a genome-wide DNAm study in paediatric-onset SLE patients across multiple blood cell lineages. The DNAm profiles of four purified immune cell lineages (CD4 + T cells, CD8 + T cells, B cells and neutrophils) and whole blood were compared in 16 Chinese patients with paediatric-onset SLE and 13 healthy controls using the Illumina HumanMethylationEPIC BeadChip. Comparison of DNAm in whole blood and within each independent cell lineage identified a consistent pattern of loss of DNAm at 21 CpG sites overlapping 15 genes, which represented a robust, disease-specific DNAm signature for paediatric-onset SLE in our cohort. In addition, cell lineage-specific changes, involving both loss and gain of DNAm, were observed in both novel genes and genes with well-described roles in SLE pathogenesis. This study also highlights the importance of studying DNAm changes in different immune cell lineages rather than only whole blood, since cell type-specific DNAm changes facilitated the elucidation of the cell type-specific molecular pathophysiology of SLE.